2017
DOI: 10.1364/oe.25.027506
|View full text |Cite
|
Sign up to set email alerts
|

Streaking of 43-attosecond soft-X-ray pulses generated by a passively CEP-stable mid-infrared driver

Abstract: Attosecond metrology has so far largely remained limited to titanium:sapphire lasers combined with an active stabilization of the carrier-envelope phase (CEP). These sources limit the achievable photon energy to ∼100 eV which is too low to access X-ray absorption edges of most second- and third-row elements which are central to chemistry, biology and material science. Therefore, intense efforts are underway to extend attosecond metrology to the soft-X-ray (SXR) domain using mid-infrared (mid-IR) drivers. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
268
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 484 publications
(299 citation statements)
references
References 42 publications
0
268
1
12
Order By: Relevance
“…Shortly after the Nobel Prize was awarded to Zewail in 1999 for the development of femtochemistry, the first experiments with attosecond laser pulses were reported, 5,6 marking the beginning of attosecond science. The shortest pulse duration reported to date amounts to only 43 attoseconds 276 . Whereas femtosecond time-resolved experiments are widely applied to study charge-transfer problems, as also shown in this review, this area has only recently moved into the focus of attosecond spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…Shortly after the Nobel Prize was awarded to Zewail in 1999 for the development of femtochemistry, the first experiments with attosecond laser pulses were reported, 5,6 marking the beginning of attosecond science. The shortest pulse duration reported to date amounts to only 43 attoseconds 276 . Whereas femtosecond time-resolved experiments are widely applied to study charge-transfer problems, as also shown in this review, this area has only recently moved into the focus of attosecond spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…Ultrashort laser sources are unique technological tools to resolve in time laser-matter dynamics on ultrafast timescales [1]. Nowadays, the highest temporal resolution of pump-probe experiments lies in the attosecond (1 as = 10 −18 s) domain and it is provided by the availability of ultrashort extreme ultraviolet (XUV) and x-ray pulses delivered either by high-order harmonic generation (HHG) in gases [2][3][4] or by Free-Electron Lasers [5,6]. HHG-based XUV attosecond pulses are routinely used in time-resolved pump-probe spectroscopic techniques to initiate dynamics, which are then probed by a second pulse at a later time.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Such successes necessitate both theoretical and experimental studies of processes of USP interaction with various objects. [1,2] Such successes necessitate both theoretical and experimental studies of processes of USP interaction with various objects.…”
Section: Introductionmentioning
confidence: 99%
“…The progress in development of the technique of generation of ultrashort electromagnetic pulses (USP) has resulted in creation of sources that can form pulses of femtosecond and attosecond duration. [1,2] Such successes necessitate both theoretical and experimental studies of processes of USP interaction with various objects. [3][4][5] One of the promising objects of USP interaction with a substance is plasma.…”
Section: Introductionmentioning
confidence: 99%